Economic Valuation and Cultivation of Persimmons in Takengon City Central Aceh District - Ayu Erfiana Asmy; Rahmadhani Fitri (Budapest International Research and Critics University, 2021)
The persimmon fruit (Diospyros kaki) or Oriental persimmon is a complex plant that lives in the wild for hundreds of years growing in Indonesia in the highlands of at least 1000 above sea level; this plant turns out to function to resist erosion, landslides, and floods because of its strong roots and form fibers inside. The soil so that can withstand soil shifts that are suppressed by water. Besides stems, seeds, fruit from persimmon is also beneficial for health. However, some of this persimmon ecosystem has been cut down because its economic value is too low for the community. The purpose of this study is to determine the monetary value of the remaining persimmon ecosystem, determine what impacts humans feel when cutting down persimmon trees and determine alternative policies with the management of persimmon cultivation in the city of Takengon. This study used a survey method; sampling was selected by purposive sampling. The analysis used is the formula for total economic value (total economic value/TEV), willingness to accept (WTA). The results of this study indicate that the total monetary value of the persimmon ecosystem area in Takengon City is Rp. 27,175,000,000/ha/yr. The estimated economic value of the persimmon area is Rp.254.316 million/year.